Effects of rapid thermal annealing on the properties of AlN films deposited by PEALD on AlGaN/GaN heterostructures. Issue 47 (27th May 2015) - Cao, Duo; Cheng, Xinhong; Xie, Ya-Hong; Zheng, Li; Wang, Zhongjian; Yu, Xinke; Wang, Jia; Shen, Dashen; Yu, Yuehui
<x xml:space="preserve">Abstract</x> AlN films are grown on AlGaN/GaN by PEALD. High-temperature annealing promotes complete nitridation of AlN film, and causes AlN to form a semiconductor-like structure.